西班牙戏剧史和中国戏剧 史的开端特征异同比较 = A Comparative Study of Early Spanish and Chinese Theatre - Xiao, Yang (Sinología hispánica. China Studies Review, 2015)
本文分析早期西班牙戏剧，即从西班牙戏 剧起源到天主教双王统治时期（出现了《塞莱 斯蒂娜》这部代表作品)的戏剧特征，同时介绍 中国戏剧的产生和发展过程。通过平行对比早 期西班牙戏剧和中国戏剧，发现两国戏剧史在 开端和初步发展阶段展示出的异同。这一对比 研究有助于更广泛地理解西班牙和中国在戏剧 历史和文学主题上的主要特征。 The paper investigates early stage of Spanish theatre, from its origins to the period of the Catholic Monarchs, where La Celestina appears is analyzed. Meanwhile the initiation and evolution of Chinese theatre are presented. Through parallel analysis of the early Spanish theatre and the early Chinese theatre, the article aims to find the similarities and differences between both sides. The comparison will help to gain a broader understanding of the historical and thematic features of the Spanish and Chinese dramas